(untitled) (Biological Sciences - PJSIR, 2000)
The role of carbon and nitrogen sources on the production of acetone and butanol by alocal strain of C.acetobutylcium was investigated. Molasses was found to be superior as compared with the othertested mono di and polysaccharides. The highest solvent yield (17.37 g 1.1) was obtained with a culture medium containing 140 g I-I molasses. (NH4)2S0 4proved to be the best inorganic nitrogen source whereby a total yield of 17.7 g I-I solvents were obtained at 2 g I-I salt level. Among the different organic nitrogen soures tested, rice bran and corn bran mixture (5 g I-I each) proved to be the best, where by 18.56 g I-I of total solvents were obtained.